Freshman Attrition in a College of Applied Arts and Technology of Ontario - Dietsche, Peter H. J. (Canadian Journal of Higher Education, 1990)
This study, conceptualized using a "person-environment fit" model of dropout, examined differentiated freshman attrition and persistence in a College of Applied Arts and Technology of Ontario. Also examined were the magnitude and timing of dropout as well as the ability of the model to explain and predict freshman attrition/persistence vs academic success/failure. The relative importance of student and institutional characteristics in the withdrawal process was also assessed. Results showed that thirty percent of the freshman cohort dropped out in the first year, with approximately half doing so in the first semester. Those variables which measured the nature of the student-institution interaction accounted for a greater amount of the variance in persistence/withdrawal than did the background and entry-level characteristics of the students alone. This confirms the validity of the "fit" model of dropout and suggests that college administrators could significantly reduce freshman attrition by carefully managing the college learning environment. Consistent with U.S. studies comparing factors influencing dropout in commuter and residential institutions, this study found academic integration and educational commitment to be of greater importance to persistence than social integration and institutional commitment. A student's intention to leave the college at mid-semester and his/her confidence in success were also found to be important determinants of freshman attrition.